Civil-Law Aspects of Agrivoltaic Contractual Arrangements under Italian Law: Between Innovation and Constraints - Tedioli, Francesco (Review of European and Comparative Law, 2025)
Under Italian law, the installation of agrivoltaic systems may be brought within the scope of agricultural enterprise only where there exists an effective, verifiable, and not merely declaratory link with the agricultural land (fondo rustico), within the meaning of Article 2135 of the Italian Civil Code. From this standpoint, the production of energy from renewable sources qualifies as a connected activity, and not as a substitute for the primary agricultural activity. Against the background of the European Union’s Common Agricultural Policy (CAP) and the EU climate and energy objectives, this article takes Italy as a case study within the EU legal framework and examines how the civil-law notion of "connected activity" can be reconciled with CAP conditionality and eligibility rules. On the basis of this principle, Italian agrivoltaic contractual practice - in particular, deeds establishing surface rights, land tenure titles, and coordination agreements - must be structured so as to ensure continuity of cultivation effective access to the land, compliance with the rules of the Common gricultural Policy (CAP) and with the rules of the Common Agricultural Policy (CAP) and with national incentive schemes (Ministerial Decree of 22 December 2023; GSE Director’s Decree No. 149 of 19 June 2025) and, at the same time, the bankabiity of the projects. The legal point of equilibrium in the Italian framework lies in translating the principles of sustainability and multifunctionality into binding contractual clauses capable of preserving the agricultural identity of the land and making energy production compatible with the economic and social function of the agricultural enterprise. The analysis also offers brief comparative insights into selected EU Member States, showing that similar tensions between dual land use (food/energy) and CAP requirements arise across Europe, and suggesting criteria for a possible future revision of Article 2135 of the Italian Civil Code in line with EU law.